Comparison of Indonesian and Finnish Education Curriculum - Vevi Sunarti; Hafizah Hafizah; Rusdinal Rusdinal; Azwar Ananda; Nurhizrah Gistituati (Goodwood Publishing, 2022)
Purpose: This study aims at describing the planning of the education system that will be adapted that it is necessary to make comparisons in order to improve the quality of the education system and contribute to the government in considering making policies to improve the Indonesian education system. Research methodology: The research design is used a case study to compare the education system between Indonesia and Finnish and literature review to collect relevant research. Results: The results of the study indicated that the Indonesian education curriculum is classified as low because it is based on five curriculum components, namely objectives, contents-materials, media, learning strategies, and learning process. Limitations: This study focuses on the five curriculum components in the Indonesian education system generally, so that there is a gap that can be filled by future researchers by discussing more deeply along with examples from other countries. Contribution: This research contributes to curriculum policyholders in the Indonesian education system because it can be a reference for improving the quality of the Indonesian education system.